2021
DOI: 10.1109/jiot.2021.3068596
|View full text |Cite
|
Sign up to set email alerts
|

5G Embraces Satellites for 6G Ubiquitous IoT: Basic Models for Integrated Satellite Terrestrial Networks

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(76 citation statements)
references
References 183 publications
(220 reference statements)
0
57
0
Order By: Relevance
“…5 SpaceX plans to use optical ISL and has completed on-orbit testing. 6 OneWeb will not use these technologies for the time being, but they claim that at some point in the deployment of the system. rate due to the limited frequency resources.…”
Section: ) Higher Frequency Bandsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 SpaceX plans to use optical ISL and has completed on-orbit testing. 6 OneWeb will not use these technologies for the time being, but they claim that at some point in the deployment of the system. rate due to the limited frequency resources.…”
Section: ) Higher Frequency Bandsmentioning
confidence: 99%
“…For the vision of 6G, it is generally recognized that terrestrial cellular networks alone cannot achieve. For example, in remote rural and barren areas, traditional terrestrial networks are still incapable of deploying and maintaining owing to their limitations of geographical location and operation cost [3], [4], [5], [6]. According to the report of Global System for Mobile Communications assembly (GMSA), more than 40% of the Earth's area is still without network coverage, and nearly 4.6 billion Internet users are looking forward to a higher rate plus lower latency network [7].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also proposed a simplified air interface protocol for IoT and a simultaneous uplink IoT communication. In Fang et al [51], discussed three basic cooperative models and techniques that can be used to implement hybrid satellite-terrestrial networks to support 5G mobile networks. The authors have also identified the challenges in implementing hybrid network to support 6G and provided an analysis of ongoing research in this area.…”
Section: Satellite-based 5g (And Beyond) Network For Iot Servicesmentioning
confidence: 99%
“…The Internet of Things (IoT) has become an importation application in 5G and beyond network [ 1 , 2 , 3 , 4 , 5 , 6 ]. With the evolution of IoT, there will be billions of connected IoT users (IoTUs), which can provide various applications, e.g., smart city, health, and agriculture.…”
Section: Introductionmentioning
confidence: 99%